Basic Leadership Training bagi Mahasiswa dengan Pendekatan Social Learning Theory - Dian Yudhawati; Arundati Shinta (Jurnal Maksipreneur, 2012)
Being a good leader is a result of learning. A good leader criterion in most of people’s head is either success in completing organizational tasks or beloved by most of members. That criterion is really difficult to be learned and then be internalized. Based on the social learning theory, one learns to be a leader through observation process as the first step. In daily activity, there are many leaders but only certain leader who is observed about his or her behaviors in detail. That observed leader usually success in completing organizational tasks and also beloved by his or her members. After observation, the next process is memorizing those behaviors. The next stage is trying to produce those behaviors. This third step can be achieved through leadership training. In that training, one is motivated to produce and imitate those behaviors. After training, one can practice the new leadership behaviors in daily activity if he or she receives behavior reinforcements. Because of those reinforcements, the new leadership behaviors will be his or her good habits. Actually, in that leadership training, one can learn either being a good leader or good member. Being a good member, one should be able to inspire either other members or leader. He or she should not be a problem source but a solution source.